2015
DOI: 10.2147/cer.s62637
|View full text |Cite
|
Sign up to set email alerts
|

Off-pump versus on-pump coronary artery bypass grafting: comparative effectiveness

Abstract: Background: Historically, coronary artery bypass grafting (CABG) with the use of cardio pulmonary bypass (CPB), referred to as onpump CABG, has been regarded as the "gold standard". However, in recent years, it has been increasingly recognized that the systemic inflammatory response associated with using CPB contributes substantially to postoperative organ dysfunction. Intuitively, performance of CABG without CPB, referred to as offpump CABG, should translate into improved clinical outcomes. Interestingly, no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…But the our present data correlates with kowalewski et al 2020 (4) Study and Giovanni et al 2017 (5) . But Raja et al 2015 (6) , Daniel et al 2016 (7) , studies doesn't correlate with the present study as these studies finds no significant difference in short term mortality between on pump and off pump The short term mortality was highest among age group of 50-69 years on patients undergone on pump cabg and 50 to 59 years for off pump cabg this is against to that of Nicolini et al 2017 (8) which shows highest mortality among 70-89 years followed by 60 to 69 years which can explained as less number of patients above 70 years have undergone procedure in present study The short term mortality was highest among on pump group patients with Ef less than 40 than off pump group correlating with Zhiyuan et al (9) it was found in this study that the left main involvement in multivessel disease had some contribution to the mortality more in on pump group . This was against with Benedetto et al 2019 (11) study and supported by yeatman et al 2001 (10)…”
Section: Discussionmentioning
confidence: 99%
“…But the our present data correlates with kowalewski et al 2020 (4) Study and Giovanni et al 2017 (5) . But Raja et al 2015 (6) , Daniel et al 2016 (7) , studies doesn't correlate with the present study as these studies finds no significant difference in short term mortality between on pump and off pump The short term mortality was highest among age group of 50-69 years on patients undergone on pump cabg and 50 to 59 years for off pump cabg this is against to that of Nicolini et al 2017 (8) which shows highest mortality among 70-89 years followed by 60 to 69 years which can explained as less number of patients above 70 years have undergone procedure in present study The short term mortality was highest among on pump group patients with Ef less than 40 than off pump group correlating with Zhiyuan et al (9) it was found in this study that the left main involvement in multivessel disease had some contribution to the mortality more in on pump group . This was against with Benedetto et al 2019 (11) study and supported by yeatman et al 2001 (10)…”
Section: Discussionmentioning
confidence: 99%
“…A good example is a study comparing outcomes from coronary artery bypass surgeries performed both with and without pumps. 16 This study concluded that outcomes from both were comparable. The journal that published this study in 2017 stopped publishing in September 2018.…”
mentioning
confidence: 79%
“…In Raja's study, off-pump CABG versus on-pump CABG is correlated with comparable short-, mid-, and long-term mortality, similar organ protection, and fewer distal anastomoses. The available evidence cannot, nonetheless, substantiate all concerns about the safety and efficacy of off-pump CABG [37].…”
Section: Type Of Technique (Off-pump Versus On-pump)mentioning
confidence: 98%